Artificial Intelligence in Civil Justice: Comparative Legal Analysis and Practical Frameworks for Indonesia - Maskanah, Ummi (Universitas Negeri Gorontalo, 2025)
The advancement of artificial intelligence (AI) technology presents opportunities to improve the efficiency and accessibility of the judicial system in civil procedural law reform. Nonetheless, its execution in Indonesia continues to encounter numerous obstacles, including infrastructure, regulatory issues, and opposition from law enforcement agencies. This study seeks to examine the impact of AI on improving access to and efficacy of justice within the framework of civil procedural law reform in Indonesia. We employ the normative legal research method, which utilizes an approach to law and literature review, to determine the potential and challenges of integrating AI into Indonesia's judicial system. Research findings suggest that AI can accelerate the litigation process and improve the uniformity of court decisions based on precise facts. To ensure optimal use of AI, comprehensive regulatory reform is necessary, along with improvements in infrastructure and training for law enforcement personnel. The findings highlight the importance of formulating policies that promote openness and ethics in AI utilization to maintain fairness principles.